Meningkatkan Nilai-Nilai Religiusitas Anak-Anak Desa Sukolilan Kecamatan Patebon Kabupaten Kendal Melalui Taman Pendidikan Al-Qur’an (TPQ) - Qothrunnada Zuhaidah; Rizqotul Khoifah; Alfiyatun Ni’mah; Intan Ayu Novitasari; M. Fajar Romadhon; Muhammad Syarif Hidayat (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of sophisticated information technology makes almost everything that happens in every corner of the world immediately known and international dependence is increasing. Therefore, it is necessary for religious education to grow and develop not only in schools but also in the family and community environment. An example of religious education that is positive and relevant to today is TPQ teaching which can facilitate children not only knowledge, but a place to play and interact between peers. This research uses a qualitative method with a participatory approach, by going directly to TPQ to teach children and making observations and collecting data which is then analyzed in a scientific way which is also concluded with scientific arguments. The result of this study is that TPQ teaching which is carried out in the afternoon makes children productive, so that the time to play with meaningless things is reduced. With a positive routine such as TPQ teaching in Sukolilan Village, it will certainly increase the sense of religiosity of children so that it can be their provision in facing modern times which are increasingly affected by global currents.